81.5k views
0 votes
Help with this question, please!

Help with this question, please!-example-1

1 Answer

6 votes

Answer:


x+2

Explanation:

If
P(x) is a polynomial and
x+a is a factor of polynomial the
p(-a)=0

check
x+3 that is
x=-3


P(-3)=-(3)^3-5(-3)^2-2(-3)+24\\=-27-5*9+6+24\\=-27-45+6+24\\=-72+30\\=-42

Hence
(x+3) is not a factor of
P(x).


Check\ (x+1)\ that\ is\ x=-1\\P(-1)=(-1)^3-5(-1)^2-2(-1)+24\\=-1-5+2+24\\=-6+26\\=20

Hence
(x+1) is not a factor of
P(x).

Check
(x+2) that is
x=-2


P(-2)=(-2)^3-5(-2)^2-2(-2)+24\\=-8-20+4+24\\=-28+28\\=0

Hence
(x+2) is a factor of
P(x).

User Shadie
by
5.5k points